Agrotourism Development in Sukalarang Village, Sukabumi Regency - Putri, Agustina Eka; Dienaputra, Reiza D; Novianti, Evi; Khadijah, Ute Lies (E-Journal of Tourism; Volume 8 Number 2 (September 2021), 2021)
The diversity of attractiveness of agricultural cultivation supported by a strategic location, unspoiled environment, mostly agricultural land, and community friendliness can be the main attraction for tourists and Sukalarang Village, Sukabumi Regency has it all. This study aims to identify the attractiveness of Sukalarang Village through agrotourism and analyze its development strategy. The qualitative method is this research approach with online primary and secondary data sources through previous research, online media, and government regulatory documents. Data collection techniques using online questionnaires and interviews. The research analysis used was qualitative and descriptive. This finding is expected to be able to answer the potential attraction of Sukalarang Village agro-tourism because the people in Sukalarang Village still make agricultural and plantation activities their daily activities and formulate development strategies as an agro-tourism village with the initiation of plantation owners and the village government. Sukalarang Village.